Magmatic-Hydrothermal Processes of Vein-Type Haman-Gunbuk-Daejang Copper Deposits in the Gyeongnam Metallogenic Belt in South Korea - Lee, Tong Ha; Seo, Jung Hun; Yoo, Bong Chul; Lee, Bum Han; Han, Seung Hee; Yang, Yun Seok; Lee, Jun Hee (Frontiers in Earth Science, 2021)
Haman, Gunbuk, and Daejang deposits are neighboring vein-type hydrothermal Cu deposits located in the SE part of the Korean Peninsula. These three deposits are formed by magmatic-hydrothermal activity associated with a series of Cretaceous granodioritic intrusions of the Jindong Granitoids, which have created a series of veins and alterations in a hornfelsed shale formation. The copper deposits have common veining and alteration features: (1) a pervasive chlorite-epidote alteration, cut by (2) Cu-Pb-Zn-bearing quartz veins with a tourmaline-biotite alteration, and (3) the latest barren calcite veins. Chalcopyrite, pyrite, and pyrrhotite are common ore minerals in the three deposits. Whereas magnetite is a dominant mineral in the Haman and Gunbuk deposits, no magnetite is present, but sphalerite and galena are abundant in the Daejang deposit. Ore-bearing quartz veins have three types of fluid inclusions: (1) liquid-rich, (2) vapor-rich, and (3) brine inclusions. Hydrothermal temperatures obtained from the brine inclusion assemblages are about 340 - 600 °C, 250 - 500 °C, and 320 - 460 °C in the Haman, Gunbuk, and Daejang deposits, respectively. The maximum temperatures (from 460 to 600 °C) recorded in the fluid inclusions of the three deposits are higher than those of the Cu ore precipitating temperature of typical porphyry-like deposits (from 300 to 400 °C). Raman spectroscopy of vapor inclusions showed the presence of CO2 and CH4 in the three deposits, which indicates relatively reduced hydrothermal conditions as compared with typical porphyry deposits. The Rb/Sr ratios and Cs concentrations of brine inclusions suggest that the Daejang deposit was formed by a later and more fractionated magma than the Haman and Gunbuk deposits, and the Daejang deposit has lower Fe/Mn ratios in brine inclusions than the Haman and Gunbuk deposits, which indicates contrasting redox conditions in hydrothermal fluids possibly caused by an interaction with a hosting shale formation. In brines, concentrations of base metals do not change significantly with temperature, which suggests that significant ore mineralization precipitation is unlikely below current exposure levels, especially at the Haman deposit.